Vascular cell adhesion molecule 1 induces T-cell antigen receptor-dependent activation of CD4+T lymphocytes. - Damle, N K (1991)
Effective stimulation of CD4+ T cells in an immune response depends on activation signals transduced via not only the CD3-T-cell receptor (TCR) complex but also those generated by accessory cell-surface proteins, including some that mediate adhesion between T cells and antigen-presenting cells (APC). Three members of the Ig superfamily, CD54 [intercellular cell adhesion molecule 1 (ICAM-1)], CD58 [lymphocyte function-associated antigen 3 (LFA-3)], and B7, expressed on the surface of APC, have been shown to mediate both adhesion and signaling during T cell-APC interactions. Recently another member of the Ig superfamily, [vascular cell adhesion molecule 1 (VCAM-1; INCAM110)], has been identified. VCAM-1 mediates adhesion between endothelial cells and activated lymphocytes and certain tumor cells. Here, using a soluble VCAM-1 fusion protein with receptor globulin (Rg), we examined the role of VCAM-1 in T-cell activation. We observed that CD4+ T cells, which are inefficiently stimulated by immobilized anti-TCR-1 or anti-CD3 monoclonal antibody (mAb) alone, can be induced to proliferate when exposed to immobilized VCAM-1-Rg in conjunction with either immobilized anti-TCR-1 or immobilized anti-CD3 mAb. The costimulatory effects of VCAM-1-Rg on CD4+T cells is inhibited by mAb to either the CD29 (integrin beta 1)-CD49d [very late activation antigen 4 alpha (VLA-4 alpha)] complex on the surface of CD4+ T cells or to VCAM-1. Stimulation of CD4+ T cells with immobilized VCAM-1-Rg and anti-TCR or -CD3 mAb results in the synthesis of both interleukin 2 (IL-2) receptors and IL-2. In addition, anti-CD25 (anti-IL-2 receptor a) mAb significantly inhibited the VCAM-1-Rg/anti-TCR or -CD3 mAb-driven activation of CD4+ T cells, indicating that endogenously produced IL-2 is in part responsible for the observed T-cell proliferation. Collectively, these results suggest that VCAM-1 can play an important costimulatory role during the activation of CD4+ T cells.